Cost‐effectiveness of prenatal screening strategies for congenital heart disease. (July 2014) - Pinto, N. M.; Nelson, R.; Puchalski, M.; Metz, T. D.; Smith, K. J.
ABSTRACT Objective The economic implications of strategies to improve prenatal screening for congenital heart disease (CHD) in low‐risk mothers have not been explored. The aim was to perform a cost‐effectiveness analysis of different screening methods. Methods We constructed a decision analytic model of CHD prenatal screening strategies (four‐chamber screen (4C), 4C + outflow, nuchal translucency (NT) or fetal echocardiography) populated with probabilities from the literature. The model included whether initial screens were interpreted by a maternal–fetal medicine (MFM) specialist and different referral strategies if they were read by a non‐MFM specialist. The primary outcome was the incremental cost per defect detected. Costs were obtained from Medicare National Fee estimates. A probabilistic sensitivity analysis was undertaken on model variables commensurate with their degree of uncertainty. Results In base–case analysis, 4C + outflow referred to an MFM specialist was the least costly strategy per defect detected. The 4C screen and the NT screen were dominated by other strategies (i.e. were more costly and less effective). Fetal echocardiography was the most effective, but most costly. On simulation of 10 000 low‐risk pregnancies, 4C + outflow screen referred to an MFM specialist remained the least costly per defect detected. For an additional 580 per defect detected, referral to cardiology after a 4C + outflow was the most cost‐effective for the majority of iterations, increasing CHD detection by 13 percentage points. Conclusions The addition of examination of the outflow tracts to second‐trimester ultrasound increases detection of CHD in the most cost‐effective manner. Strategies to improve outflow‐tract imaging and to refer with the most efficiency may be the best way to improve detection at a population level. Copyright © 2013 ISUOG. Published by John Wiley & Sons Ltd.